Controlling Pollution : Using Taxes and Tradable Permits - Reppelin, Valerie (Economic Issues; Economic Issues ;, 2001)
Explores different ways of controlling pollution through -green-taxes or permits, and evaluates their advantages and disadvantages. While many countries use environmental taxes, interest in tradable permits is growing.